Analisis Inovasi Produk Dan Media Promosi Dalam Meningkatkan Penjualan UMKM Kota Surakarta - Febrita Putri Ayu Navatiana; Susilo, Agus (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes product innovation and promotional strategies of three MSMEs in Surakarta to boost sales and competitiveness. Using a qualitative case study approach, findings reveal that new product variants, improved packaging, and alignment with local preferences combined with creative digital promotions via social media and marketplaces significantly enhance sales and customer loyalty. The study highlights that adaptive, context-specific marketing strategies, supported by ongoing innovation and digital technology, are essential for MSME sustainability in the digital economy.